French as a Second Language in the Formation of Spanish-Speaking Engineers: A Premiere [el Francés Como Segunda Lengua en la Formación de de Ingenieros Hispano-Parlantes: Un Debut] - Canete-Arratia, L (2012)
With the purpose of increasing the intellectual capital of Spanish-speaking engineers, alternatives for teaching French are evaluated as harmonic and formal part of technological programs in a Chilean university. Since no information was available about the costs and benefits that the inclusion of a second foreign language would bring in their professional performances, different designs of the subject were analyzed. Through simulations and experiments with volunteers, it was found that the best alternative is to include French once the students finish the first year of their careers, with four hours per week, achieving an intermediate level. This option shows that the average income of young graduates would increase by more than 7%, extending their communications network, expanding their cultural wealth and decreasing class discrimination, among other positive impacts.